Navigating Organizational Change: An analytical study of the influence of change Management Strategies on Employee Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Official university libraries are the only official entities responsible for ensuring the safety of learning outcomes through the services they provide to their patrons, and this poses a significant challenge to the study's stated goal of improving performance. The study's significance lies in the fact that libraries are influenced by various external factors; specifically, the study's theme is changing management, and the study's recommendations and results have the potential to yield substantial financial gains that would benefit the Indian community at large. Using a case study of Indian university libraries, this research sought to determine how change management affected staff productivity. The study focused on three types of change: organizational, technological, and personal. The research strategy used in this study was a descriptive survey. We used stratified random sampling to choose 311 people at random from the whole population. The data collected from a structured questionnaire using a five-point Likert scale was analyzed using regression analysis.